Quantitative Study of Load Stability of Quadrotor Based on Lyapunov Exponents - Tiantian Dong; Yonghong Zhang; Yunping Liu; Cheng Chen (International Journal of Antennas and Propagation)
This paper addresses the issue of dynamic instability in quadrotor caused by changes in load mass during flight. To tackle this problem, the Lyapunov exponent method is adopted to study the dynamics and motion stability of the system. This approach resolves the challenge of constructing system eigenvalues due to the nonlinearity and high order of the quadrotor. To enhance the reliability of stability analysis, a quantitative relationship between system dynamics parameters and motion stability is established by combining the dynamic model with the Lyapunov exponent method. This approach compensates for inaccuracies in theoretical modeling analysis caused by factors such as load mass changes. The experiments demonstrate that changing the wheelbase and load mass improves flight motion stability, ensuring the reliability of the quadrotor flight system. Overall, this paper provides an in-depth analysis of the motion stability of a quadrotor and proposes a reliable method for stability analysis that accounts for changes in load mass during flight.